المشكلات التي تواجه طلبة كلية التربية بجامعة تشرين أثناء تطبيق التربية العملية في المدارس من وجهة نظر الطلبة أنفسهم - كشيك, منى; بكور, محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت الدراسة إلى التعرف إلى المشكلات التي تواجه طلبة كلية التربية في جامعة تشرين أثناء تطبيق التربية العملية في المدارس؛ وذلك من وجهة نظر الطلبة أنفسهم. وقد استخدم الباحث المنهج الوصفي التحليلي، وطوّر استبانة مؤلفة من (48) بنداً, وموزعة على أربعة مجالات, هي: الإشراف، وإدارة المدرسة، والإعداد المهني، وطلبة المدارس. وطبقها على عينة مكونة من (150) طالباً وطالبة من طلبة السنة الرابعة/ تخصص معلم صف. وقد أظهرت نتائج الدراسة عموماً أن أهم المشكلات التي يعاني منها طلبة كلية التربية بجامعة تشرين أثناء تطبيق التربية العملية في المدارس, هي: ضعف متابعة المشرف لملاحظاته التي يبديها للطلبة المعلمين أثناء الزيارة الصفية، وعدم توفير إدارة المدرسة للأدوات والوسائل التعليمية اللازمة أثناء تطبيق التربية العملية، وعدم اهتمام إدارة المدرسة بمواظبة الطالب المعلم أثناء التربية العملية، وعدم إشراك الطالب المعلم في الأنشطة المدرسية خارج الدوام الرسمي، وأخيراً عدم التزام الطلبة بتنفيذ الواجبات البيتية التي يكلفهم بها الطالب المعلم . The purpose of this study isreconizingthe problems which face students of Education college at Tishreen University during applying Practicum education at schools from the student's point of view , and acknowledge of differences points of view according tothese problems on the basis of gender school year . As also researcher method of descriptive and analysis, besides researcher has developed statement involved from (48) items distribute on fourth fields supervision, school management, professional preparation, school students . As he applies on a sample consist of (150) male and female students from the third and fourth year specializing at class teacherThe results showed that in general the most important problems experienced by students of the Faculty of Education at Tishreen University during the application of practical education in schools: the scarcity of follow-up supervisor for the remarks expressed by student teachers during the classrooms visit, lack of school management and educational tools needed during the application of practical education, lack of interest in school administration assiduously student teacher during the process of education, lack of involvement of the student teacher in school activities outside of working hours, lack of commitment to the implementation of students' homework assigned thereto by the student teacher